Share Repurchases and Insider Trading Behavior: Evidence from Korea - Kim, Kyung Soon; Lee, Jin Hwon; Kim, Yu-Jin; Park, Yun W. (Korean Journal of Financial Studies, 2023)
Using the context of open-market share repurchases in Korea, we examine insider trading behavior around share repurchase disclosures. In particular, we investigate managerial opportunism as a motivation for share repurchases by analyzing how insider trading behavior differs between direct share repurchases with a strong signal effect and indirect share repurchases with a weak signal effect. We obtained the following research findings. First, in direct share repurchases, insiders become net sellers after share repurchase disclosure. Second, insider net selling is the highest when a company’s stock is overvalued rather than when its liquidity is the highest. Third, insider buy trades are followed by insider sell trades in direct share repurchases. Fourth, this negative relationship is more pronounced in firms with low ownership concentration. Finally, in direct share repurchases, opportunistic firms experience inferior stock performance compared with non-opportunistic firms. Overall, our findings support the managerial opportunism hypothesis, that is, in direct share repurchases, managers engage in informed trades based on the market confirmation bias that a share repurchase is a signal of undervaluation.